The woman hunter - Kowalski, Bernard, 1929-2007; Eden, Barbara, 1934-; Vaughn, Robert, 1932-; Bing Crosby Productions; Cinetel Films ([Los Angeles, CA] : Bing Crosby Productions, Inc., 1972)
While vacationing in Mexico, a wealthy woman realizes that the artist hired to paint her portrait has designs on her jewels-- or perhaps on her life.
Barbara Eden, Robert Vaughn, Stuart Whitman, Sydney Chaplin, Enrique Lucero, Larry Storch.
Cinematographer, Gabriel Torres; editor, Melvin Shapiro; music, George Duning.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Jewel thieves -- Drama; Vacations -- Mexico -- Drama; Mexico -- Drama; Thrillers (Television programs); Made-for-TV movies; Detective and mystery television programs; Internet videos; Streaming video